Identifikasi Morfologi Jamur Kontaminan pada Naskah Lontar - PUTRA, I KOMANG VIDIA DHARMA TARO; SUDIARTA, I PUTU; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2021)
Morphological Identification of Fungal Contaminant in Lontar Manuscripts The lontar manuscript is a cultural heritage of Balinese ancestors that contains knowledge that includes mantras, traditional medicine, songs and religious history. The physical condition of the lontar manuscript is very susceptible to being damaged by fungi. The fungus that grows on lontar manuscripts is thought to be of the species: Fusarium, Penicillium, and Aspergillus flavus. The purpose of this study was to determine the type of fungus that attacks lontar palm. The study began with sterilization of the instrument, manufacture of PDA media, isolation of pathogenic fungi, Koch's postulate test on palm lontar manuscripts, identification of morphology. The results showed that the fungus contained in the lontar manuscript is a type of fungus Penicillium sp. it can be seen from the identification results that the fungus has the following characteristics: white and brownish orange colonies, has insulated hyphae, erect and insulated conidiophores, conidia are chain-shaped and congregate on top of phialids.